2015
DOI: 10.1080/14680629.2015.1021368
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and rheological properties of aged and unaged polymer-modified asphalt binders

Abstract: The effects of ageing on the microstructure and dynamic rheological properties of three modified asphalt binders are investigated. The asphalt modifiers used comprise crumb rubber (CR), styrene-butadiene-styrene (SBS) block copolymer and a blend or combination of CR and SBS (CCR). To investigate the modified asphalts microstructure, scanning electron microscopy is applied, while for assessing rheological properties at a wide range of temperature, Bending Beam Rheometry and Dynamic Shear Rheometry are employed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…However, when comparing the modified binders, the rubber asphalt should provide a better resistance to rutting than the SBS binder. Wang et al (2015) observed similar trends when comparing rubber asphalt and SBS binders. as an initiative to improve mixture design, uses the performance grade (PG) system to select asphalt binders based on the expected pavement temperatures.…”
Section: Methodssupporting
confidence: 62%
“…However, when comparing the modified binders, the rubber asphalt should provide a better resistance to rutting than the SBS binder. Wang et al (2015) observed similar trends when comparing rubber asphalt and SBS binders. as an initiative to improve mixture design, uses the performance grade (PG) system to select asphalt binders based on the expected pavement temperatures.…”
Section: Methodssupporting
confidence: 62%
“…Therefore, it is more suitable for simulating the aging of large-void permeable asphalt pavements and HVMA in comparison with the PAV test . In the weathering aging test, the aging caused by temperature is almost the same as standard PAV aging. ,, The effect of humidity and solar radiation is the unique feature of weathering aging compared with PAV aging. Humidity is not a significant aging factor in weathering aging.…”
Section: Introductionmentioning
confidence: 99%
“…11 In the weathering aging test, the aging caused by temperature is almost the same as standard PAV aging. 10,15,16 The effect of humidity and solar radiation is the unique feature of weathering aging compared with PAV aging. Humidity is not a significant aging factor in weathering aging.…”
Section: ■ Introductionmentioning
confidence: 99%
“…One of the effective methods is to use various modifiers to decrease the stiffness modulus of asphalt at low temperatures and increase the complex modulus at high temperatures. Therefore, modified asphalt is being vigorously developed as an alternative road construction material [ 5 ]. Styrene–butadiene–styrene (SBS) copolymers are the most common modifiers used to enhance the performance and extend the service life of asphalt pavements [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%